2020
DOI: 10.1002/pssr.202000459
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Photochromic Performance of Yttrium Oxyhydride Thin Films

Abstract: Yttrium oxyhydride (YHO) is a rare‐earth‐metal oxyhydride that has attracted considerable attention due to its outstanding photochromic properties. The transparency of YHO thin films across the infrared and visible spectral regions is reduced considerably under UV illumination (photodarkening) and recovers when the illumination is removed (bleaching). Although oxygen diffusion has been shown to be necessary for these processes, the exact mechanism for the photochromic behavior is not yet understood. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…However, this scenario is excluded because Baba et al . reported that the absorbance of YO x H y decreases even at 5 K by the illumination of UV light (λ = 405 nm) …”
Section: Resultsmentioning
confidence: 99%
“…However, this scenario is excluded because Baba et al . reported that the absorbance of YO x H y decreases even at 5 K by the illumination of UV light (λ = 405 nm) …”
Section: Resultsmentioning
confidence: 99%
“…Later, the same group of authors suggested-based on photodarkening results obtained at low temperatures (5 K)-that a simple anion transfer out of the film cannot be responsible for the photochromic process. [22] Herein, we show that encapsulated photochromic REHO films with transparent, nonphotochromic, and thin diffusion barriers perform equally well as uncapped films. Moreover, we prove that the films sealed against the environment are still photochromic and long-time stable as oxidation is inhibited by the diffusion barrier.…”
Section: Introductionmentioning
confidence: 77%
“…In line with this idea, we note that during illumination, the Gd oxyhydride films reach a conductivity (∽10 −1 Scm −1 ) which is not far from that (∽10 −2 Scm −1 ) of a GdO x H 3 − 2x //GdH x mixedphase sample purposely produced as a reference (Figure S8, Supporting Information). Furthermore, the light-induced volume contraction, and the slow [6,13] temperature activated [20,21] kinetics would follow from the necessary structural rearrangements. The time dependence of the bleaching can be connected to the average rate of disappearance of the metallic domains.…”
Section: Hypothesis Of Metallic Phase Segregationmentioning
confidence: 99%